2006
DOI: 10.1111/j.1365-2222.2006.02526.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged exclusive breastfeeding is associated with increased atopic dermatitis: a prospective follow‐up study of unselected healthy newborns from birth to age 20 years

Abstract: Prolonging strictly exclusive breastfeeding for > or =9 months was not helpful in atopy prevention, instead, it was associated with increased atopic dermatitis and food hypersensitivity symptoms in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
1
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 47 publications
(55 reference statements)
5
68
1
5
Order By: Relevance
“…9 However, a study on 200 newborns in Finland found that prolonging strictly exclusive breastfeeding for dermatitis and food hypersensitivity symptoms in childhood. 10 Our results were in agreement with the Swedish study, but only examined the effect of breastfeeding for 6 months, not longer durations.…”
Section: Discussionsupporting
confidence: 82%
“…9 However, a study on 200 newborns in Finland found that prolonging strictly exclusive breastfeeding for dermatitis and food hypersensitivity symptoms in childhood. 10 Our results were in agreement with the Swedish study, but only examined the effect of breastfeeding for 6 months, not longer durations.…”
Section: Discussionsupporting
confidence: 82%
“…25,26 Conflicting findings have been reported from several studies investigating the associations between breastfeeding and the development of allergic diseases. 6,7,27,28 …”
Section: Figurementioning
confidence: 99%
“…2 Some prospective studies supported neither prolonged breastfeeding nor delayed introduction of solid foods for the prevention of allergic diseases in children. [4][5][6][7] Conversely, increased risk for atopic dermatitis, eczema, and allergic sensitization (with or without symptoms) has been associated with delayed introduction of egg, milk, cereals, and other solids. 1,[3][4][5]8 The concept of reverse causality is an important consideration in evaluation of the association between the timing of the introduction of solid foods and the development of allergic diseases in cohort studies.…”
mentioning
confidence: 99%
“…However, some studies have not confirmed this protective effect of breastfeeding. [8][9][10][11][12] Others, paradoxically, suggest that breastfeeding may promote disease development. 9.12 These conflicting findings suggest that the presence of factors not yet fully understood are implicated in the development and progression of AD, such as colonization of the atopic child with bacteria through breastfeeding, among them S. aureus.…”
Section: Introductionmentioning
confidence: 99%